2022
DOI: 10.3390/su14106312
|View full text |Cite
|
Sign up to set email alerts
|

Which Is the Best Supply Chain Policy: Carbon Tax, or a Low-Carbon Subsidy?

Abstract: The low-carbon supply chain is key to promoting sustainable development and solving environmental pollution. Government policies related to lowering carbon emissions deeply affect supply chains. This paper builds a supply chain decision-making model under three different regulatory policies: a pure carbon tax, a pure low-carbon subsidy, and a mixed policy with both a carbon tax and a low-carbon subsidy, then compares and analyzes the impacts of these three different regulatory policies on carbon emissions, man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The customer with awareness of low-carbon consumption prefers to buy the products from environment-friendly parties and this change motivates the rest of members in the supply chain to promote the green activity programs. We observe that lot of literature (Wang et al, 2019, De Giovanni and Zaccour, 2013, Ji et al, 2017, Wu et al, 2022 are concentrating on the interaction between two prominent supply chain members -manufactures and retailers. One possible reason is that these two members are of larger importance in steering the economic activities.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The customer with awareness of low-carbon consumption prefers to buy the products from environment-friendly parties and this change motivates the rest of members in the supply chain to promote the green activity programs. We observe that lot of literature (Wang et al, 2019, De Giovanni and Zaccour, 2013, Ji et al, 2017, Wu et al, 2022 are concentrating on the interaction between two prominent supply chain members -manufactures and retailers. One possible reason is that these two members are of larger importance in steering the economic activities.…”
Section: Introductionmentioning
confidence: 94%
“…There is also a description about duel channel supply chain (Ji et al, 2017) in which the products can be brought to the market through online and retailer two channels taking into account the current growth of e-commerce. Moreover, on the basis of these models, the constraints or policies which the supply chain is utilized to accomplish the green upgrade can be diverse, such as carbon tax (Wang et al, 2019, Wu et al, 2022, cap-and-trade (Ghosh et al, 2020, Zhang et al, 2021, green supply chain management (Herrmann et al, 2021, Zhao et al, 2012, consumers' low-carbon preference (Ghosh et al, 2020, Ji et al, 2017, Wang et al, 2019, Ye et al, 2017, lowcarbon subsidy (Wu et al, 2022, Zhu et al, 2011, green activity program and contract design (De Giovanni and Zaccour, 2013). The trade-off mechanism designed in (Su and Parilina, 2023) is exactly learning from contract design, in which the retailer share the manufacturer's sales profit and the cost of green activities.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [13] explored the effects of a carbon tax, certified emissionabatement (CEA) costs, and consumers' low-carbon preferences on low-carbon decision making, and the results of the study showed that supply chains benefited from increased consumer environmental awareness, but increased CEA costs were detrimental to supply chain profit growth. Wu et al [14] constructed a model of supply chain decision making under three different regulatory policies, namely, pure carbon tax, pure low-carbon subsidy, and a mixture of carbon tax and low-carbon subsidy, and comparatively analyzed their impacts. The authors of [15,16] studied the coordination problems of green supply chains and designed contracts to promote the cooperation of green supply chain members and improve supply chain performance.…”
Section: Green Supply Chainmentioning
confidence: 99%
“…The carbon cap-and-trade model created by Wu et al accounts for product inventory and routing considerations. The model can reduce carbon dioxide emissions and operational costs [74].…”
Section: Cap-and-tradementioning
confidence: 99%